Transistor mismatch effect on common-mode gain of cross-coupled amplifie - Zainul Abidin; Eka Maulana; Ramadhani Kurniawan Subroto; Wijono Wijono (Universitas Ahmad Dahlan, 2019)
In this paper, the analytical approach of MOS transistor mismatch effect on common-mode gain of cross-coupled amplifier is presented. Transconductance (MOS transistor parameter) mismatch effect on common-mode gain of cross-coupled amplifier was analyzed. This study was started with mathematical derivation for representing the mismatch effect of transconductance between 2 differential pairs of crosscoupled amplifier due to common-mode voltage. The derivation result was simulated based on Monte Carlo simulation with random transconductance mismatch rate from 0.05% until 1%. The common-mode gain increases 36.9 dB and average common-mode gain is -81.1 dB. The transconductance mismatch rate increases followed by increase in common-mode gain. The results can be used by circuit designers to design analog circuits, especially operational amplifier used for biosignals processing to minimize the common-mode gain of their circuits. This research presents aid to circuit designers to improve their circuits performance.